Programmed instruction on the English past tense for grade five - Vergara, Ruperta (Robles) 1936- ([Quezon City publisher not identified], 1973)
This study is about a programmed text on the English Past Tense which was modestly attempted at constructing self-instructional materials for grade five learners of English as a Second language. The programmed text is of the linear type. The revised text now contains one hundred and thirty three frames arranged sequentially such that each stimulus produces a gradual increase in the mastery of the past tense. Immediate feedback is provided for pupils to register the correct answer.
Thesis (Master in Education)--University of the Philippines.
Keywords: English language -- Programmed instruction; English language -- Study and teaching (Elementary).